Dinamika Penggunaan Dana Bantuan oleh DPD/DPW Partai Politik di Provinsi Bangka Belitung pada Tahun 2020 - Tampubolon, Alexander Oktovianus (Indonesian Democracy Research Center, 2022)
Political parties are political platforms to compete for power through electoral contestation. The relationship between political parties and political life is fundamental in a democratic country. Every year political parties receive assistance funds sourced from the State / Regional Budget with the aim of providing political education and operationalizing the secretariat. Researchers want to know how each party maximizes the use of funds based on the provisions stipulated in Permendagri number 36 of 2018. The purpose of this study is to observe the dynamics of the use of aid funds by DPD / DPW political parties in the province of Riau Islands in 2020. Political party assistance funds in the calculation procedures, budgeting in the regional revenue and expenditure budget, and orderly administration of submission, distribution, and accountability reports for the use of political party financial assistance are regulated in Permendagri number 36 of 2018. The theory used in this research is the theory of modern political party management from Hofmeister and Grabow. This research uses descriptive qualitative research methods to find out the dynamics of the use of aid funds by DPD / DPW political parties in the province of bangka Belitung islands in 2020. The data collection techniques used were observation, interviews, and documentation.The results of the research in this journal based on interviews and data from BPK representatives of the province of Bangka Belitung explain that there are two (2) political parties that have not been adequate in the use of aid funds and seven (7) political parties have been adequate in the use of these aid funds.